Comparison of Intense Pulsed Light with 1, 927‐nm Fractionated Thulium Fiber Laser for the Rejuvenation of the Chest. Issue 2 (19th December 2013) - Wu, Douglas C.; Friedmann, Daniel P.; Fabi, Sabrina G.; Goldman, Mitchel P.; Fitzpatrick, Richard E.
<x xml:space="preserve">Abstract</x> Background Rejuvenation of the aging chest is important to prevent noticeable disparities between the treated skin of the face and that of the untreated chest. Objective To compare a high‐density thulium fiber laser (TFL)‐based protocol for the rejuvenation of the aging chest with intense pulsed light (IPL). Methods and materials We conducted a retrospective chart review comparing patients treated with IPL and those treated with TFL in combination with a quality‐switched alexandrite laser and long pulsed dye laser. Blinded photographic assessment of overall improvement, rhytides, skin texture, dyspigmentation, and telangiectasia was performed. Patient satisfaction was assessed in a standardized follow‐up survey. Cost and practicality were compared. Results At a mean follow‐up of 45.8 days for IPL and 78.3 days for TFL, the two protocols had comparable clinical efficacy in achieving rejuvenation of the chest. Differences existed in terms of cost and practicality. Conclusion TFL can be used at high density and in simultaneous combination with other targeted laser modalities to achieve rejuvenation of the aging chest. IPL achieves similar clinical efficacy. The choice between treatment modalities depends on physician and patient preferences.